2010
DOI: 10.1128/mcb.00966-10
|View full text |Cite
|
Sign up to set email alerts
|

A TFIIH-Associated Mediator Head Is a Basal Factor of Small Nuclear Spliced Leader RNA Gene Transcription in Early-Diverged Trypanosomes

Abstract: Genome annotation suggested that early-diverged kinetoplastids possess a reduced set of basal transcription factors. More recent work, however, on the lethal parasite Trypanosoma brucei identified extremely divergent orthologs of TBP, TFIIA, TFIIB, and TFIIH which, together with the small nuclear RNA-activating protein complex, form a transcription preinitiation complex (PIC) at the spliced leader (SL) RNA gene (SLRNA) promoter. The SL RNA is a small nuclear RNA and a trans splicing substrate for the maturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…TFIIH/CDK7-mediated CTD phosphorylation disrupts this interaction, presumably facilitating promoter escape of the polymerase (56). Trypanosomes do possess a mediator complex that is essential for SLRNA transcription, interacts with TFIIH, and is required for the formation of a transcription preinitiation complex at the SLRNA promoter (18). However, whereas the eukaryotic mediator consists of head, middle, tail, and CDK8 modules, electron microscopic structure analysis of the trypanosome complex indicated that it is confined to the head module (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TFIIH/CDK7-mediated CTD phosphorylation disrupts this interaction, presumably facilitating promoter escape of the polymerase (56). Trypanosomes do possess a mediator complex that is essential for SLRNA transcription, interacts with TFIIH, and is required for the formation of a transcription preinitiation complex at the SLRNA promoter (18). However, whereas the eukaryotic mediator consists of head, middle, tail, and CDK8 modules, electron microscopic structure analysis of the trypanosome complex indicated that it is confined to the head module (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the absence of a TFIIH kinase (17) and the presence of a minimal mediator complex suggest that, in trypanosomes, a mediator-CTD interaction does not occur and a release of RNA Pol II from the mediator is not a prerequisite for promoter escape of the enzyme. Accordingly, tandem affinity purification of the trypanosome mediator did not copurify detectable amounts of RNA Pol II subunits (18), and vice versa (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only acquiring the structural information, single particle EM is ideally suited to characterize the conformation of Mediator under different conditions and illuminate how it is affected by interaction with various factors. Understanding the interaction of Mediator with the general RNAPII machinery has derived from EM structures of the Mediator-RNAPII complex (Davis et al, 2002;Bernecky et al, 2011), Mediator-TFIIH complex (Lee et al, 2010), Mediator Head-TBP , and Mediator Head-RNAPII (Cai et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%